The Use of Monoclonal Antibodies to Human Platelet Membrane Glycoprotein IIb-IIIa to Quantitate Platelet Deposition on Artificial Surfaces - Mulvihill, Juliette N; Huisman, Han G; Cazenave, Jean-Pierre; van Mourik, Jan A; van Aken, Willem G (Thrombosis and Haemostasis, 1987)
A new technique is described to quantitate platelet deposition in vitro on artifical surfaces, based on a surface phase radioimmunoassay using the monoclonal antibody 6C9, directed specifically against the membrane glycoprotein complex IIb-IIIa of human platelets. Results correlate in linear fashion with those obtained using 111Indium labeled platelets. The method offers particular advantages for the measurement of platelet deposition in whole blood, since platelet separation, washing and labeling procedures are eliminated, together with the ensuing possible selection of platelet populations. In vitro perfusion is performed in glass capillaries of precisely defined diameter (0.80 or 0.56 mm i.d.). Blood flow is laminar and accurately controlled over wall shear rates ranging from venous to capillary (50-4,000 s-1). Using glass capillaries precoated with purified human albumin or fibrinogen or bovine collagen, platelet deposition from suspensions of washed human platelets in Tyrode's-albumin buffer in the presence of a 40% hematocrit is (platelets/mm2): 11,000 (albumin), 78,000 (fibrinogen) and 306,000 (collagen) after 5 min perfusion at 2,000 s-1. In heparin, citrate or hirudin anticoagulated whole blood, surfaces are passivated, probably by albumin adsorption from plasma (platelets/mm2): 400 (albumin), 3,600 (fibrinogen) and 48,000 (collagen) after 5 min perfusion in the presence of 13 mM citrate.
Keywords: Platelet deposition; Thrombosis; Monoclonal antibody; Glycoprotein IIb-IIIa; Biomaterials; Capillary perfusion